Fiberglass pipe design. (American Water Works Association, 2005)
Annotation "AWWA Manual M45, Fiberglass Pipe Design, provides the reader with technical and general information to aid in the design, specification, procurement, installation, and understanding of fiberglass pipe and fittings. It is intended for use by utilities and municipalities of all sizes, whether as a reference book or textbook for those not fully familiar with fiberglass pipe and fitting products. Design engineers and consultants may use this manual in preparing plans and specifications for new fiberglass pipe design projects. The manual covers fiberglass pipe and fitting products and certain appurtenances, and their application to practical installations, whether of a standard or special nature."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Revised edition of: Fiberglass pipe design manual. ©1996.
Keywords: Water-pipes -- Design and construction.; Reinforced plastics.; Glass fibers.; elektronické knihy; electronic books